A study of height, weight and body mass index in Nepalese - Baral, Prakash; Shrestha, Rami; Shrestha, Ratindra Nath; Banstola, Dinesh; Prajapati, Rajesh (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: The height measurement is an important anthropometric measurement which can be directly correlated with health status of an individual. Body weight of an individual refers to total body mass and is also important indicator of health status of people. Body mass index (BMI) is a key index for relating weight to height. It is defined as the body mass divided by the square of the body height, The BMI is an attempt to quantify the amount of body tissue mass  in an individual, and then categorize that the person as underweight, normal weight, overweight or obese.Objectives: To find out the average height and weight, to calculate BMI and find out its average value and to correlate height and weight in Nepalese population.Methodology: A cross sectional study was conducted in subjects from different parts of Nepal. Three hundred twenty one healthy subjects of 25-40 years of age group were studied. Height and weight of subjects were recorded and BMI was calculated. Data were analyzed using SPSS.Result: In overall Nepalese population, Mean height was found to be 156.6 ± 6.3 cm; mean weight 56.6 ± 11.4 kg and BMI 20.9 ± 1.8 kg/m2. Pearson’s correlation co-efficient(r) for height and weight was 0.88.Conclusion: There was partial positive correlation between height and weight. There was statistically significant difference in height, weight and BMI between Nepalese male and female(p